Beyond p-hexaphenylenes: synthesis of unsubstituted p-nonaphenylene by a precursor protocol - Abdulkarim, Ali; Nathusius, Marvin; Bäuerle, Rainer; Strunk, Karl-Philipp; Beck, Sebastian; Räder, Hans Joachim; Pucci, Annemarie; Melzer, Christian; Jänsch, Daniel; Freudenberg, Jan; Bunz, Uwe H. F.; Müllen, Klaus (Chemistry - a European journal, 2021)
The synthesis of unsubstituted oligo-para-phenylenes (OPP) exceeding para-hexaphenylene—in the literature often referred to as p-sexiphenyl—has long remained elusive due to their insolubility. We report the first preparation of unsubstituted para-nonaphenylenes (9PPs) by extending our precursor route to poly-para-phenylenes (PPP) to a discrete oligomer. Two geometric isomers of methoxylated syn- and anti-cyclohexadienylenes were synthesized, from which 9PP was obtained via thermal aromatization in thin films. 9PP was characterized via optical, infrared and solid-state 13C NMR spectroscopy as well as atomic force microscopy and mass spectrometry, and compared to polymeric analogues. Due to the lack of substitution, para-nonaphenylene, irrespective of the precursor isomer employed, displays pronounced aggregation in the solid state. Intermolecular excitonic coupling leads to formation of H-type aggregates, red-shifting emission of the films to greenish. 9PP allows to study the structure-property relationship of para-phenylene oligomers and polymers, especially since the optical properties of PPP depend on the molecular shape of the precursor.